A computational model of a domestic solar heating system with underground spherical thermal storage - Inalli, M; Unsal, M; Tanyildizi, V (Pergamon-Elsevier Science Ltd, 1997)
This theoretical study deals with a domestic heating system assisted by solar energy stored in an underground spherical container. The system includes a heat pump. The analytical model employed calculates the water temperature in the storage vessel, as well as the temperature distribution in the surrounding geological structure, by using the monthly-average solar radiation and ambient temperature. Storage temperature, collector efficiency, performance coefficient of the heat pump (COP) and annual solar fraction are computed and presented in various graphs. The importance of seasonal solar energy storing in the ground is demonstrated. (C) 1997 Elsevier Science Ltd.